Utilization of natural stimulants on crab survival and molting acceleration: progresses and challenges - Said Ali Akbar; Cut Nuzlia; Sari Afriani; Ilham Zulfahmi (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2024)
This study investigates the potential of natural stimulants, specifically ecdysteroids, in accelerating the molting process in mangrove crabs. The research was conducted by analyzing various plants containing ecdysterone and their effects on the crabs. The results indicate that forest fern leaves and mulberry leaves are effective sources of ecdysterone in stimulating molting and growth in crabs. The use of such natural stimulants has the potential to enhance productivity and reduce reliance on synthetic hormones in crab cultivation. However, further research is needed to determine the optimal dosage and to understand the mechanisms of ecdysterone action in crabs in more detail. The main challenge in implementation is adjusting the dosage and frequency of natural stimulant administration to achieve optimal results without disrupting the balance of the cultivation ecosystem. This approach offers an environmentally friendly alternative for the sustainable development of crab farming.